INTEGRASI FILOSOFI BUDAYA LOKAL MELALUI GAMIFIKASI DIGITAL DALAM PEMBELAJARAN IPAS SEKOLAH DASAR: TINJAUAN LITERATUR SISTEMATIS - Suwitno Dedi Nababan; Unsa Sabrina; Eko Handoyo; Indriana Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The transition to 21st-century education calls for the transformation of interactive digital media to accommodate shifts in the learning styles of Year 5 primary school pupils. However, the dominance of global content in digital media poses a threat to the erosion of local cultural identity. This study aims to investigate, map, and synthesise strategies and the effectiveness of integrating local cultural philosophy (ethnoscience) through digital gamification in the Natural and Social Sciences (IPAS) curriculum. This study employs a Systematic Literature Review (SLR) design, adopting the standard PRISMA reporting protocol. Research trends and collaboration networks were mapped through bibliometric analysis using the VOSviewer software. A review of various primary literature sources indicates that: (1) there is a growing need to develop culture-based interactive media to address the gap in the literature regarding game mechanics; (2) the most effective strategy for cultural integration is to convert local philosophical values into game rules, mission narratives, and reward systems, rather than merely visual embellishments; and (3) the fusion of gamification and ethnoscience has been empirically proven to enhance students’ cognitive understanding of abstract scientific concepts, whilst simultaneously boosting intrinsic motivation and the relevance of learning. The conclusions of this study affirm that gamification infused with local wisdom is an innovative pedagogical solution that not only improves academic achievement in IPAS but also serves as an instrument for cultural preservation in the digital age.